2020
DOI: 10.3390/en13071797
|View full text |Cite
|
Sign up to set email alerts
|

Study on the Tri-axial Time-Dependent Deformation and Constitutive Model of Glauberite Salt Rock under the Coupled Effects of Compression and Dissolution

Abstract: Solution mining for glauberite salt rock is a long-term process that takes several years to several decades. Therefore, deposit deformations and subsidence of ground surfaces are time-dependent deformation problems that should consider the effect of water dissolution. In order to investigate the time-dependent deformation characteristics of glauberite salt rock, tri-axial time-dependent deformation tests were conducted under the condition of 4 MPa confining pressure and 5 MPa axial pressure with infiltration p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 31 publications
0
1
0
Order By: Relevance
“…There has been extensive research on the interaction between water and rocks, focusing primarily on the following aspects: microstructural evolution of rocks under water-rock interactions [4][5][6][7], the static mechanical behavior of rocks under water-rock interactions [8][9][10][11], the dynamic behavior of rocks under water-rock interactions [8,12,13], and the physical and chemical interaction mechanisms between water and rocks [2,14,15]. It can be concluded that the presence of water to some extent disrupts the macroscopic and mesoscopic structure of rocks, weakening the mechanical properties.…”
Section: Introductionmentioning
confidence: 99%
“…There has been extensive research on the interaction between water and rocks, focusing primarily on the following aspects: microstructural evolution of rocks under water-rock interactions [4][5][6][7], the static mechanical behavior of rocks under water-rock interactions [8][9][10][11], the dynamic behavior of rocks under water-rock interactions [8,12,13], and the physical and chemical interaction mechanisms between water and rocks [2,14,15]. It can be concluded that the presence of water to some extent disrupts the macroscopic and mesoscopic structure of rocks, weakening the mechanical properties.…”
Section: Introductionmentioning
confidence: 99%